2004
DOI: 10.1080/07853890410018899
|View full text |Cite
|
Sign up to set email alerts
|

The Caveolin genes: from cell biology to medicine

Abstract: Caveolae are vesicular organelles (50-100-nm in diameter) that are particularly abundant in cells of the cardiovascular system, including endothelial cells, smooth muscle cells, macrophages, cardiac myocytes and fibroblasts. In these cell types, caveolae function both in protein trafficking and signal transduction, as well as in cholesterol homeostasis. Caveolins are the structural proteins that are both necessary and sufficient for the formation of caveolae membrane domains. Caveolins 1 and 2 are co-expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
318
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(327 citation statements)
references
References 85 publications
(95 reference statements)
5
318
2
2
Order By: Relevance
“…We next analyzed the effects of ozone inhalation on expression of Cav-1, a membrane scaffolding protein known to negatively regulate PI3K and p44/42 MAPK (Williams and Lisanti, 2004;Schwencke et al, 2006). Western blot analysis revealed that alveolar macrophages from air exposed wild type mice constitutively expressed Cav-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next analyzed the effects of ozone inhalation on expression of Cav-1, a membrane scaffolding protein known to negatively regulate PI3K and p44/42 MAPK (Williams and Lisanti, 2004;Schwencke et al, 2006). Western blot analysis revealed that alveolar macrophages from air exposed wild type mice constitutively expressed Cav-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that macrophages from transgenic mice with a targeted disruption of the gene for TNFα were unable to generate reactive nitrogen intermediates and that these mice were protected from ozone toxicity. This was associated with a marked attenuation of ozone-induced activation of PI3K/PKB and p44/42 MAPK and suppression of caveolin-1 (Cav-1), a negative regulator of TNFα signaling (Williams and Lisanti, 2004). These findings are novel and may lead to the identification of new targets for therapeutic intervention aimed at regulating lung inflammation induced by pulmonary irritants.…”
Section: Introductionmentioning
confidence: 94%
“…There are three known isoforms of caveolin: caveolin-1, caveolin-2 and caveolin-3 [9], each of which has scaffolding domains that interact with signaling molecules [10,11]. Cardiac myocytes (CM) express the muscle-specific isoform caveolin-3 [12] while other cell types in the heart express caveolin-1 and -2.…”
Section: Introductionmentioning
confidence: 99%
“…The caveolins serve as membrane scaffolding proteins that compartmentalise various signalling molecules within discrete domains at the plasmalemma, termed caveolae [12]. Specifically, caveolin-1 is known to generally repress the inherent kinase activity of a number of proto-oncogenes through binding of the kinase catalytic regions to a contiguous twenty amino acid motif situated within the N-terminus of the caveolin-1 molecule, termed the caveolin scaffolding domain [13].…”
Section: Introductionmentioning
confidence: 99%